2022
DOI: 10.3758/s13414-022-02516-0
|View full text |Cite
|
Sign up to set email alerts
|

Tau and kappa in interception – how perceptual spatiotemporal interrelations affect movements

Abstract: Batting and catching are real-life examples of interception. Due to latencies between the processing of sensory input and the corresponding motor response, successful interception requires accurate spatiotemporal prediction. However, spatiotemporal predictions can be subject to bias. For instance, the more spatially distant two sequentially presented objects are, the longer the interval between their presentations is perceived (kappa effect) and vice versa (tau effect). In this study, we deployed these phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…To this end, the authors in a previous study 5 compared both the Tau and Kappa effects elicited by concurrent visual-tactile stimulation using a shared setup and complementary experimental tasks on space and time perception. Results showed that the Tau effect was only seldom elicited especially in the visual modality, in agreement with recent findings 6 . Conversely, the Kappa effect was consistently elicited across modalities, however suggesting different magnitudes related to the modality involved.…”
Section: Introductionsupporting
confidence: 92%
“…To this end, the authors in a previous study 5 compared both the Tau and Kappa effects elicited by concurrent visual-tactile stimulation using a shared setup and complementary experimental tasks on space and time perception. Results showed that the Tau effect was only seldom elicited especially in the visual modality, in agreement with recent findings 6 . Conversely, the Kappa effect was consistently elicited across modalities, however suggesting different magnitudes related to the modality involved.…”
Section: Introductionsupporting
confidence: 92%
“…This interpretation is supported by additional analyses, 5 showing no correlations between location anticipation and speed estimates, further corroborating that these judgments are likely based on different processes. An additional suggestion for future research to examine these processes would be to re-run this task, but employ a different dependent variable, namely temporal estimates of when participants think the ball would land or the object would change direction following racket/ball contact (for example, see Schroeger et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Illusions are valuable tools for studying perception mechanisms since one can relate neural responses to both the physical aspects of the stimuli and subject's answers (Rajala et al, 2013). In contrast to visual illusions (e.g., change-blindness illusion (O'Regan et al, 1999)) and multisensory illusions (such as kappa and tau effects (Schroeger et al, 2022)), which are well-known and extensively studied, there is limited understanding of spatial auditory illusions and the mechanisms underlying them (Rajala et al, 2013). As the spatial representation of auditory signals does not occur at the receptor level (Grothe et al, 2010), this may make designing experiments a challenge.…”
Section: Introductionmentioning
confidence: 99%